Análisis del Sistema Nacional de Compras Públicas. un estudio probabilístico de la adjudicación de contratos - Banderas Benítez, María Fernanda (2019)
In order to manage the economic resources in a transparent and efficient way, the LOSNCP in 2007 creates the INCOP, currently called SERCOP. Although the World Bank qualifies it as number one at the continent level, there are investigations that affirm the presence of flaws in the system. The present work has as objective to verify if the random system for processes of minor amount of works correctly, in addition, to find the probability of gain of a bidder and to find if there is some incidence in the number of contracts won with the cost and final term of the projects. The methodology was developed in three stages: in the first stage the formula of Laplace was applied to find the probability of gain of a bidder, the second stage consisted of a visual analysis by means of radial graphs that involve the number of contracts won and the increases of costs in the processes, in addition through tables, the percentage of works that were delivered both inside and outside the term established in the contract was identified. Finally, the binomial probability was obtained by bidder and the calculation of the Pearson correlation coefficient for grouped data was subsequently performed. The results showed that the probability of gain is inversely proportional to the number of bidders in the draw, there is no relationship between the number of contracts won with the fulfillment of the cost and the term, the statistical analysis of the random process allows us to presume the existence of failures in the SERCOP.